Willingness of Healthcare Workers to Recommend or Receive a Third COVID-19 Vaccine Dose: A Cross-Sectional Study from Jordan - Mohammad Abu Lubad; Munir A. Abu-Helalah; Israa F. Alahmad; Malak M. Al-Tamimi; Mohammad S. QawaQzeh; Ahlam M. Al-kharabsheh; Hamed Alzoubi; Ahmad H. Alnawafleh; Khalid A. Kheirallah (MDPI AG, 2023)
Background: The availability of COVID-19 vaccines worldwide necessitates measuring healthcare workers' (HCWs') willingness to recommend or receive these vaccines. Therefore, we conducted a local study in Jordan to assess HCWs' willingness to recommend or receive a third dose of a COVID-19 vaccine and the predictors of such a decision. A cross-sectional study investigated Jordanian HCWs' willingness regarding a third dose of a COVID-19 vaccine using a self-administered online questionnaire through WhatsApp, a mobile phone application. A total of 300 HCWs participated in the current study. Of these HCWs, 65.3% were physicians, 25.3% were nurses, and 9.3% were pharmacists. HCWs' overall willingness regarding a third vaccine dose was 68.4% (49.4% certainly and 19.0% probably), whereas the overall willingness of HCWs to recommend a third dose to their patients was 73.3% (49.0% certainly and 24.3% probably). Males had significantly higher willingness than females (82.1% vs. 60.1%, p < 0.05). Physicians reported more willingness than nurses and pharmacists. HCWs' willingness was not significantly affected by direct contact with a patient infected with COVID-19 or by a personal history of COVID-19 infection. Only 31% of HCWs were certainly willing to recommend the vaccine to their patients with chronic diseases, and only 28% of the participants were certainly willing to recommend it to people aged 65 or older. HCWs' willingness to receive a third dose of a COVID-19 vaccine is limited in Jordan. This has affected their certainty in recommending this vaccine to their patients or people older than 60. Decision-makers and health-promotion programs in Jordan should focus on addressing this public health problem.